Analysis of factors affecting the welfare of farmers and craftsmen in Naga village, Neglasari village, subdistrict, Tasikmalaya regency - Supriyadi, Encep; Dewanti, Diah Setyawati; Mubarrok, Wafiyulloh (Indonesian Journal Publisher, 2023)
This research has an important meaning to assess the welfare side of agriculture and craftsmen, which will later be seen as elements that affect the welfare of farmers and craftsmen. This study aims to determine the level of welfare of farmers and craftsmen in Naga Village, Neglasari Village, Salawu District, Tasikmalaya Regency. The method in this study is qualitative. Data collection uses observation, interview, and documentation techniques using purposive sampling methods. The data is processed using qualitative analysis tools, namely atlas.ti and SWOT analysis. The results of this study found that the level of welfare of farmers and craftsmen is influenced by the amount of production and income of farmers and craftsmen themselves. The problem of farmers in Naga Village currently carrying out agricultural productivity is the lack of help from people to help harvest rice. As for the craftsmen, no serious problems were found, it's just that if there is no bamboo, they have to wait first. The results of the SWOT analysis show that the government, farmers and craftsmen are important cooperate in increasing the productivity of agriculture and craftsmen in Naga Village.